The logistics evolution : implications and challenges for the local trucking industry. - Lee, Sea Cheu. (2008)
Amidst a backdrop of rapid technological advancements, the logistics industry is undergoing radical transformations at a frenetic pace. This project serves to chronicle the events that has shaped the industry the way it is today and and anticipate the direction it will be heading in the future. In addition, this project further explores the feasibility of an Internet portal capable of improving information exchange and facilitating collaboration amongst local logistics service providers. Though there are certain drawbacks and limitations to the portal, research evidence suggest that the portal is a highly feasible idea in the local context.